A microscopic level insight into Pt doped TiZn (001) surface for hydrogen energy storage usage. Issue 77 (2nd August 2016) - Verdinelli, V.; Juan, A.; Marchetti, J. M.; Germán, E.
Abstract : H-storage behavior on TiZn and Pt-doped TiZn alloys. Abstract : The interaction of hydrogen and platinum with B2–TiZn (001) surface was studied by means of spin-polarized density functional theory (DFT) calculations. H and Pt on TiZn adsorption energies were calculated taking into account high symmetry adsorption sites. Both the adatoms prefer to be adsorbed on the hollow site where the higher coordination number allows them to minimize the repulsion among the overlapping charge densities of them and the surface. Furthermore, the influence of pre-adsorbed Pt on the H adsorption was analyzed in detail. It was found that this process is enhanced in Pt doped TiZn surface. The electronic structures and changes in the chemical bonding for both the adsorbates on the Ti alloy surface were computed by density of states (DOS) and overlap population (OP) methods, concluding that 3d x 2 − y 2, 3d z 2 and 3p z Ti, 5p z Pt orbitals play an important role in H adsorption, as well as it was deduced that the strong overlap between Pt and Ti orbitals allows H atoms to bond more effectively on the surface. Bader's analysis revealed that H and Pt act as electron acceptors, whereas surface Ti-atoms act as electron donors during the H adsorption process.